Pengaruh dalam Pemenuhan Tanggung Jawab Pelaku Usaha Terhadap Standar Kualitas Air Minum - Sindi Pulumuduyo; Nirwan Junus; Abdul Hamid Tome (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research aims to find out how business actors fulfill their responsibilities on drinking water quality standards. This research is empirical research because it places primary data in the community as the main data, which is analyzed descriptively. The results of the research show that the factors influencing the fulfillment of the legal responsibilities of drinking water depot refill business actors regarding drinking water quality standards in the city of Gorontalo are the lack of public knowledge and understanding regarding the quality of healthy drinking water, as well as what rights they can obtain regarding the existence of a business offered; and weak supervision and provision of sanctions, which are still minimally carried out by the competent authorities. This means that supervision of the location of refill drinking water depots is still minimal, and sanctions have not been strictly enforced.